(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Tradition and Modernity are two differentiating components that prevail in practically every one of the novels of R. K. Narayan. Reading his novels starts a feeling of Indianness gave his very own taste, flavour and acknowledgment of rich cultural inheritance. R.K. Narayan is one of those fortunate writers who accomplished acknowledgment with the absolute first novel, Swami and Friends. His Novels-Swami and Friends, The English Teacher, The Dark Room, The Bachelor of Arts, The Vendor of Sweets – are the novels of local life. The Financial Expert, Mr. Sampath, The Guide and The Man Eater of Malgudi manage the vocations of money chasing men of the world. Sitting tight for the Mahatma presented the incomparable Mahatma however it doesn’t turn into a political novel Narayan is neither a reformer like Mulk Raj Anand nor a philosopher like Raja Rao. He isn’t focused on any belief system. His fiction is really an artistic disclosure of a brain and its milieu. His novels are realistic without a tinge of sentimentalism or a pinch of the puzzling. He artistically depicts man’s presence and development in a world of conflicting values. Narayan has a place with this class through his perception. It is his view that essayist ought to watch internal and external parts of life and attempt to feel the current situation with brain of mass.